Determination of heat transfer coefficient using experimental values of pressure drop of a single phase fluid - Muhammad Bisharul Hafi, Ab Jalil (2010)
Analogical procedure to obtain the heat transfer coefficient for fluid flowing inside tube in turbulent range with carbon nanotubes is carried out. A regression equation valid for both water and nanofluid is developed by making use of Colburn analogy to estimate the Nusselt number. Heat transfer coefficient and pressure drop with carbon nanotubes has been analogically determined with different Prandtl number and volume concentration. Based on the analysis, the regression equation showed considerable deviation with the Gnielinski correlation and considered reliable in turbulent flow for single-phase fluid. The results also showed that convective heat transfer flow in plain tube is enhanced significantly by the existence of carbon nanotubes when compared with water using the regression equation developed. It is also observed that heat transfer coefficient for carbon nanotubes having volume concentration of 0.1% is 48.16% higher compared with water at 20,000 Reynolds number. Heat transfer coefficient is also enhanced with the increase of Prandtl number and volume concentration with maximum value of 0.5%.